Non-random vibration analysis of rotate vector reducer - Zhang, Dequan; Li, Xing-ao; Yang, Meide; Wang, Fang; Han, Xu (Journal of sound and vibration, 2023)
•A non-random vibration analysis method for RV reducer is proposed.•The interval process models are employed to characterize uncertain excitations.•A non-random vibration analysis model of RV reducer is established.•The response bounds of core components of RV reducer can be efficiently solved.•The proposed method can provide guidance during the design stage of RV reducer.•The dependence on the experimental data of RV reducer can be greatly reduced. Vibration has been and still is a persistent problem to negate the transmission accuracy and service life of rotate vector (RV) reducer, and vibration analysis remains a challenge in industry. It is attributed to the inherent structural characteristics of RV reducer. Acquisition of experimental data on core components is not straightforward. Thus, the probability-based random vibration method is no longer applicable, and vibration problem of RV is yet to be tackled. To this gap, this study proposes a non-random vibration analysis method for RV reducer, which circumvents the demand of a significant amount of experimental data via random vibration analysis method. To start with, an interval process model is introduced to establish the non-random vibration analysis model for RV reducer on the basis of the deterministic vibration model. Non-random vibration analysis method for RV reducer is then proposed by combining the deterministic vibration analysis approach with the interval process theory. The proposed non-random vibration analysis method is exemplified with a RV-20E reducer to analyze the vibration of its core components. The results are verified against Monte Carlo simulation (MCS) method to indicate that the currently proposed method can efficiently evaluate the vibration of core components inside RV reducer subject to uncertain excitation in the premise of compliance to specific design guidance.